Exposure to polycyclic aromatic hydrocarbons, DNA methylation and heart rate variability among non-current smokers. (1st November 2021) - Liu, Kang; Jiang, Jing; Lin, Yuhui; Liu, Wei; Zhu, Xiaoyan; Zhang, Yizhi; Jiang, Haijing; Yu, Kuai; Liu, Xuezhen; Zhou, Min; Yuan, Yu; Long, Pinpin; et al.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) exposure is associated with heart rate variability (HRV) reduction, a widely used marker of cardiovascular autonomic dysfunction. The role of DNA methylation in the relationship between PAHs exposure and decreased HRV is largely unknown. This study aims to explore epigenome-wide DNA methylation changes associated with PAHs exposure and further evaluate their associations with HRV alternations among non-current smokers. We measured 10 mono-hydroxylated PAHs (OH-PAHs) in urine and DNA methylation levels in blood leukocytes among participants from three panels of Chinese non-current smokers (152 in WHZH, 99 in SY, and 53 in COW). We conducted linear regression analyses between DNA methylation and OH-PAHs metabolites with adjustment for age, gender, body mass index, drinking, blood cell counts, and surrogate variables in each panel separately, and combined the results by using inverse-variance weighted fixed-effect meta-analysis to obtain estimates of effect size. The median value of total OH-PAHs ranged from 0.92 × 10 −2 in SY panel (62.6% men) to 13.82 × 10 −2 μmol/mmol creatinine in COW panel (43.4% men). The results showed that methylation levels of cg18223625 ( COL20A1 ) and cg07805771 ( SLC16A1 ) were significantly or marginally significantly associated with urinary 2-hydroxynaphthalene [β(SE) = 0.431(0.074) and 0.354(0.068), FDR = 0.016 and 0.056, respectively], while methylation level of cg09235308 ( PLEC1 ) was positively associated with urinary total OH-PAHs [β(SE) = 0.478(0.079), FDR = 0.004]. Hypermethylations of cg18223625, cg07805771, and cg09235308 were inversely associated with HRV indices among the WHZH and COW non-current smokers. However, we did not observe significant epigenome-wide associations for the other 9 urinary OH-PAHs. These findings provide new evidence that PAHs exposure is linked to differential DNA methylation, which may help better understand the influences of PAHs exposure on HRV alternations. Graphical abstract: Image 1 Highlights: Hypermethylations at cg18223625 and cg07805771 are associated with urinary 2-OH-Nap. Hypermethylation at cg09235308 is associated with urinary total OH-PAHs levels. Hypermethylations of cg18223625, cg07805771, and cg09235308 are inversely linked to HRV. DNA methylation may play a role in PAHs exposure-related adverse health effect. Abstract : Capsule: PAHs exposure is linked to differential DNA methylation, which may contribute to a better understanding of the associations between PAHs exposure and reduced HRV.